Effect of Compound Polyethylene Glycol Electrolyte Powder on the Quality of Gastrobowel Preparation before Enteroscopy Intervention - Yongxin Yuan; Yuqin Li; Yafeng Zhang; Jing Jiang; Yi He; Yimei Liao; Wenchun Yao (Emergency Medicine International)
Objective. To study the effect of compound polyethylene glycol electrolyte powder (PGEP) on the quality of gastrobowel preparation before enteroscopy intervention. Methods. From March 2021 to January 2022, among the patients who needed enteroscopy in our hospital, 280 patients who volunteered for this study were randomly selected as the research objects. All the subjects were randomly divided into the control group (140 cases) and the observation group (140 cases). Both groups received routine treatment before enteroscopy intervention. On this basis, patients in the control group were given 9 g of senna every day before operation, and 250 ml of 20% mannitol and 2500 ml of water were taken orally from 9:00 am to 11:00 am on the day of examination. Patients in the observation group took PGEP orally from 9:00 am to 11:00 am. The effective rate of bowel cleaning, the frequency of defecation and duration of diarrhea, the levels of blood electrolyte indexes such as Na+, K+, and Cl− before and after the intervention, and the incidence of adverse reactions were compared between the two groups. Results. The effective rate of bowel cleaning in the observation group was significantly higher than that in the control group (P<0.05). The frequency of defecation and duration of diarrhea in the observation group were significantly lower than those in the control group (P<0.05). Compared with the control group, the levels of blood electrolyte indexes in the observation group after the intervention were not statistically significant (P>0.05). The incidence of adverse reactions in the observation group was significantly lower than that in the control group (P<0.05). Conclusion. Using PGEP for gastrobowel preparation before enteroscopy intervention can achieve high bowel cleaning efficiency, short bowel preparation time, and low incidence of adverse reactions, which does not affect the water-electrolyte balance of patients, and the psychological state of patients before enteroscopy intervention is more stable. This program is worthy of clinical promotion.